2004
DOI: 10.1093/jn/134.3.674
|View full text |Cite
|
Sign up to set email alerts
|

Conjugated Linoleic Acid Blocks Estrogen Signaling in Human Breast Cancer Cells

Abstract: Conjugated linoleic acid (CLA), a mixture of positional and geometric isomers of linoleic acid found in dairy products and meat from ruminants, has been widely shown to possess anticarcinogenic activity against breast cancer both in vitro and in animal models. However, little information is available concerning the mechanisms of the antitumor effects of these compounds. In this study, we investigated whether CLA has direct antiestrogenic activity in estrogen receptor positive (ER+) breast cancer cells. Treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
52
0
3

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(57 citation statements)
references
References 35 publications
2
52
0
3
Order By: Relevance
“…Taken together, these data lead us to conclude that the most physiologically important anti-aromatase phytochemical in mushrooms is conjugated linoleic acid or its derivatives. In addition to its action as an aromatase inhibitor, conjugated linoleic acid has been reported to modulate estrogen receptor function, leading to the suppression of proliferation in MCF-7 cells (43,44). Liu and Sidell (45) have shown that conjugated linoleic acid can also modulate estrogen receptor phosphorylation and, therefore, activity.…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, these data lead us to conclude that the most physiologically important anti-aromatase phytochemical in mushrooms is conjugated linoleic acid or its derivatives. In addition to its action as an aromatase inhibitor, conjugated linoleic acid has been reported to modulate estrogen receptor function, leading to the suppression of proliferation in MCF-7 cells (43,44). Liu and Sidell (45) have shown that conjugated linoleic acid can also modulate estrogen receptor phosphorylation and, therefore, activity.…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have reported that has biological beneficial effects, including anticancer activity. LA inhibits the initiation, promotion, and progression phases in mammary tumors [14].In addition, LA showed anticancer activity [16], especially by its antiproliferative activity [17] and by inducing apoptosis in breast cancer cells [18].LA was demonstrated to not only inhibit the growth of hepatoma cell but also induce apoptosis in colorectal cell line [19,20]. A study of human leukemic cells MOLT-4 showed that palmitic acid inhibited DNA topoisomerase I and induced apoptosis [20], however in human lung adenocarcinoma cell line A549, palmitic acid only inhibited DNA topoisomerase I without inducing apoptosis [21].…”
Section: Discussionmentioning
confidence: 99%
“…CLA treatment of MCF-7 breast cancer cells was shown to increase protein levels of the anti-proliferative PPARγ and decrease protein levels of the anti-apoptotic PPARβ/δ [67,68]. CLA also increased the localization of PPARγ from the cytosol to the nucleus, and increased PPAR response element activation [68,69]. Use of a PPARγ antagonist abolished the growth inhibitory effects of CLA [68].…”
Section: Activation Of Peroxisome Proliferator-activated Receptorsmentioning
confidence: 97%